2019
DOI: 10.1016/j.joen.2019.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heated Sodium Hypochlorite on the Viscoelastic Properties of Dentin Evaluated Using Dynamic Mechanical Analysis

Abstract: Introduction: This study aimed to investigate the effect of immersion of standardised dentin bars in 5% sodium hypochlorite (NaOCl) solutions at 60°C and 80°C on their viscoelastic properties, using Dynamic Mechanical Analysis (DMA). Methods: Eighteen intact teeth were used to produce ninety-nine dentin bars of standard dimensions (12mm×1mm×2mm) and randomly allocated to 6 groups (n=15 each) for immersion in: (1) Saline at 26°C; (2) Saline at 60°C; (3) Saline at 80°C; (4) NaOCl at 26°C; (5) NaOCl at 60°C; (6) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Previous studies testing the effect of NaOCl on dentin strength have been conducted by immersing specimens in NaOCl solution rather than using NaOCl as a root canal irrigant [ 14 , 15 ]. The results of such studies are clinically irrelevant, as the entire specimen is subjected to NaOCl, rather than just the internal dentinal root canal wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies testing the effect of NaOCl on dentin strength have been conducted by immersing specimens in NaOCl solution rather than using NaOCl as a root canal irrigant [ 14 , 15 ]. The results of such studies are clinically irrelevant, as the entire specimen is subjected to NaOCl, rather than just the internal dentinal root canal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the effect of heated NaOCl on the mechanical properties of dentin. In these studies, dentin bars were prepared and totally immersed within the solution [ 14 , 15 ]. This methodology does not replicate the clinical scenario, during which NaOCl irrigation contacts only the internal dentinal surface of the root canal.…”
Section: Introductionmentioning
confidence: 99%
“…Decoronation was done for all teeth to ensure a straight line access during root canal preparation. Sodium hypochlorite was not used as an irrigant in the current study as it negatively affects the mechanical properties and specifically the elastic behavior of dentin (18) . Acrylic tubes were filled with vinyl polysiloxane in order to mimic the physiologic movement of periodontal membrane space during root canal preparation.…”
Section: Discussionmentioning
confidence: 99%
“…It can be heated outside / prewarmed using a beaker on a hot plate, or kettle or with a baby bottle warmer. [20,21,22] and then introduced in the canal. The extraoral heating was ineffective as it could not maintain the rised temperature of the preheated hypochlorite inside the canal and attains the equilibrium within seconds.…”
Section: Sodium Hypochlorite and Heat -mentioning
confidence: 99%
“…They found that the storage modulus was were reduced by 4.3 -6.8 GPa and 5.1 -9.7 GPa at 60°C and 80°C respectively. [22] Semra Sevimay et al (2010) stated that the surface tension of hypochlorite decreases with an increase in temperature. [41] Ling Zou et al (2010) measured the penetration of hypochlorite at 20°C, 37°C, and 45°C.…”
Section: Effect Of Heat On Viscosity Surface Tension and Penetration Of Sodium Hypochlorite -mentioning
confidence: 99%